Empowering Rural Communities through Coffee Bean Processing Training for Competitive Value Creation in Motung Village, Toba Regency - Hengki Mangiring Parulian Simarmata; Henry Dunan Pardede; Doris Yolanda Saragih; Firinta Togatorop; Daulat Nathanael Banjarnahor (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service program was designed to strengthen the competitive value of coffee bean processing through a combination of practical field training and structured mentoring for rural communities. The activity took place on June 29, 2025, in Motung Village, Ajibata District, Toba Regency, and involved 20 local participants representing farming households. The implementation model emphasized a participatory and hands-on approach, where participants were directly engaged in coffee bean processing techniques under the guidance of academic experts and field mentors. This initiative was a collaborative effort between Universitas Murni Teguh PSDKU Pematangsiantar, Politeknik Bisnis Indonesia, and the Farmer and Fishermen Association (KTNA) Pematangsiantar. The program’s primary objectives were to enhance local community skills in post-harvest coffee processing, to raise product quality standards, and to generate added value that would enable rural producers to compete in wider markets. Through structured mentoring, participants received continuous assistance that ensured they could apply the acquired knowledge and skills independently after the training activities concluded. The results demonstrated significant improvements in participants’ understanding and technical capacity, particularly in the areas of sorting, drying, roasting, and packaging coffee beans. These competencies allowed the local community to produce higher-quality coffee products that meet market expectations and enhance competitiveness. Furthermore, the program strengthened the link between academic knowledge, practical field skills, and local wisdom, which together form the foundation for sustainable rural empowerment. By improving coffee bean processing capacity, the initiative is expected to increase household income, foster an entrepreneurial spirit, and support the long-term development of Toba’s rural economy. In this way, the program not only equips the community with technical expertise but also contributes to broader goals of economic sustainability and social resilience in the region.